OPTIMIZATION OF LASER CUTTING ENGRAVING PERFORMANCE WITH ACRYLIC MATERIAL USING THE TAGUCHI METHOD APPROACH - Bagas Jaya Buwono; Budhi Martana; Muhammad Arifudin Lukmana (Center for Study and Journal Management FTI UMI, 2022)
Today's laser cutting machining process is often utilized in large industries as well as individual and student scientific projects. Acrylic is one of the materials whose processing involves a lot of laser cutting, but currently many laser cutting, especially low power ones, are not optimally optimized. In this study, the author wants to optimize laser cutting with 6.5 Watt power using the Taguchi optimization method on solid black acrylic material with a thickness of 3 mm, with reference to the surface roughness value of the workpiece after being subjected to the laser cutting process using the Ra unit. The control factors included are laser distance, laser power, cutting speed and cooling time. The experimental process was carried out 27 times with replication of measurements 2 times. The best result from the experiment was the roughness measurement value of 0.782 µm while the mean roughness value was 2.271 µm. After conducting the experiment, it is known that the best results are obtained with a laser distance factor of 20.6mm, cutting speed of 70 mm/min, laser power of 6.5 watts and cooling time of 10 s. Meanwhile, the effect of factors on the surface roughness results is the laser distance 27%, cutting speed 40.9%, laser power 18.9% and cooling time 7.05%. After calibrating the laser cutting, the cutting accuracy increased from ± 1mm to ± 0.4 mm or an increase of 60%, with an average final dimension measurement of 24.87 mm.